Effect of soybean protein on blood pressure in postmenopausal women: a meta-analysis of randomized controlled trials. Issue 8 (4th July 2017) - Kou, Tingyan; Wang, Qiuzhen; Cai, Jing; Song, Jiaqi; Du, Baoli; Zhao, Kun; Ma, Yan; Geng, Bo; Zhang, Yu; Han, Xiaohong; Jiang, Menglu; Guo, Haiyan; et al.
Abstract : Soy protein intakes ≥25 g d −1 significantly decreased SBP and DBP, which may be due to the isoflavones component. Abstract : The effect of soybean protein on blood pressure (BP) in postmenopausal women is controversial, so we aimed to conduct a systematic review and a meta-analysis of published randomized controlled trials (RCTs) to investigate whether supplementation with soy protein improves their blood pressure. PubMed and Embase were searched up to February 2016. Weighted mean differences were calculated for net changes in BP by using fixed-effect or random-effect models. Subgroup and meta-regression analyses were performed to clarify heterogeneity among the trials. A total of twelve trials (1551 postmenopausal women participants) were included in the present meta-analysis. The overall pooled estimates of the effect of soy protein indicated a significant effect on systolic blood pressure (SBP) (mean difference: −3.03 mmHg; 95% CI: −5.03, −1.02; P = 0.003) and diastolic blood pressure (DBP) (mean difference: −0.71 mmHg; 95% CI: −1.26, −0.16; P = 0.012). Subgroup analyses further demonstrated that soy protein intake ≥25 g d −1 significantly reduced BP, and the mean difference in SBP and DBP was −4.62 mmHg (95% CI: −8.42, −0.81; P = 0.04) and −1.63 mmHg (95% CI: −2.85, −0.41; P = 0.009), respectively. Soy isoflavone intake ≥100 mg d −1 had a better reduction effect both in SBP (−5.47 mmHg; 95% CI: −8.42, −2.51; P = 0.00) and DBP (−2.03 mmHg; 95% CI: −3.35, −0.72; P = 0.002). However, soy protein intake <25 g d −1 or soy isoflavone intake <100 mg d −1 had no such effects ( P > 0.05). This meta-analysis suggests that ingestion of ≥25 g soy protein per day has BP-lowering effects, and the improvements in BP may be due to the isoflavones component of soy protein. More high-quality RCTs need to be carried out to confirm the present findings.